Estimation of Genetic Parameters among Intra and Interspecific Progenies of Tree Willows - Choudhary, Punit; Singh, N. B.; Sharma, J. P.; Verma, Archna (Indian Forester, 2016)
In the present investigation seed and nursery parameters were analyzed to determine relative performance of nine hybrids of tree willows. Analysis of variance for different nursery growth traits of the important crosses revealed significant variations among full-sib families. Germination percentage showed the widest range of values (33.40-85.00%, mean 60.84%) whereas internodal length recorded the narrowest range (0.78-2.84 cm mean 1.72 cm). Plant height exhibited the maximum (291.21%) genotypic coefficient of variation while the minimum was noticed for internodal length (39.95%). Maximum phenotypic coefficient of variation (291.52%) was exhibited by number of leaves while the minimum (40.58%) was estimated for internodal length. Heritability percentage (broad-sense) was maximum in plant height (99.79%) whereas, minimum was recorded by number of leaves (87.73%). Germination percentage had the maximum genetic advance (40.86) while the minimum genetic advance was exhibited for internodal length (1.06). Maximum genetic gain was observed in plant height (114.3%) while the minimum was recorded in leaf area (57.56%). Collar diameter was found significantly positive correlated with germination percentage and survival percentage at both genotypic (0.847 and 0.868) and phenotypic (0.838 and 0.861) levels respectively. Cross Salix. matsudana (PN-227) x S. matsudana (PN-722) exhibited maximum magnitude of heterosis for survival percentage, plant height, leaf area, number of leaves and internodal length.